Study of charged-current ep interactions at Q(2)>200 GeV2 with the ZEUS detector at HERA - Derrick, M; Krakauer, D; Magill, S; Mikunas, D; Musgrave, B; Okrasinski, JR; Repond, J; Stanek, R; Talaga, R; Zhang, H; Mattingly, M; Antonioli, P; et al. (1996)
Deep inelastic charged-current reactions have been studied in e+p and e-p collisions at a center of mass energy of about 300GeV in the kinematic region Q2>200GeV2 and x>0.006 using the ZEUS detector at HERA. The integrated cross sections for Q2>200GeV2 are found to be Mathematical expression and Mathematical expression. Differential cross sections have been measured as functions of the variables x, y and Q2. From the measured differential cross sections dσ/dQ2, the W boson mass is determined to be Mathematical expression. Measured jet rates and transverse energy profiles agree with model predictions. A search for charged-current interactions with a large rapidity gap yielded one candidate event, corresponding to a cross section of Mathematical expression © 1996 Springer-Verlag.